CompTIA A+ : practice question Core 1 (220-1101) and Core 2 (220-1102) - Prowse, David L. (Exam cram (Pearson Education, Inc.), 2023)
CompTIA® A+® Practice Questions Exam Cram Core 1 (220-1101) and Core 2 (220-1102) complements any CompTIA A+ study plan with 480 practice test questions in the book plus two bonus exams on the companion websiteall supported by complete explanations of every answer. These highly realistic questions cover every area of knowledge for both CompTIA A+ exams: 220-1101 and 220-1102.